2014
DOI: 10.1136/gutjnl-2013-305715
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of MiR-429 promotes liver tumour-initiating cell properties by targeting Rb binding protein 4

Abstract: Epigenetic modification of miR-429 can manipulate liver T-ICs by targeting the RBBP4/E2F1/OCT4 axis. This miRNA might be targeted to inactivate T-ICs, thus providing a novel strategy for HCC prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 41 publications
0
101
0
Order By: Relevance
“…Accumulating evidence supports the involvement of some miRNAs in the regulation of CSC function (30,31); in particular, reduced let-7 expression was associated with tumorinitiating cells after the initiation of chemotherapy in breast cancer, and is thought to result in the maintenance of their undifferentiated status and proliferative potential (32). Similarly, miR-429 contributes to hepatocyte self-renewal, malignant proliferation, tumorigenicity, and chemoresistance, making it an attractive potential target to inactivate tumor-initiating cells in the liver (33). We show that miR-644a functions as an upstream activator of the Wnt/b-catenin pathway in ESCC, a pathway well characterized in the development of stem cell-like properties in a wide variety of cancer types, including ESCC (25,26).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence supports the involvement of some miRNAs in the regulation of CSC function (30,31); in particular, reduced let-7 expression was associated with tumorinitiating cells after the initiation of chemotherapy in breast cancer, and is thought to result in the maintenance of their undifferentiated status and proliferative potential (32). Similarly, miR-429 contributes to hepatocyte self-renewal, malignant proliferation, tumorigenicity, and chemoresistance, making it an attractive potential target to inactivate tumor-initiating cells in the liver (33). We show that miR-644a functions as an upstream activator of the Wnt/b-catenin pathway in ESCC, a pathway well characterized in the development of stem cell-like properties in a wide variety of cancer types, including ESCC (25,26).…”
Section: Discussionmentioning
confidence: 97%
“…Intriguingly, miR-429 secreted by high-expressing liver T-ICs has the potential of turning into a proactive signaling molecule to mediate intercellular communication through microvesicle (MV)-mediated intercellular exchange, and providing a permissive niche for malignant transformation of surrounding normal hepatocytes. Moreover, secreted miR-429 can be absorbed into circulation and developed as a noninvasive diagnostic biomarker for HCC [67].…”
Section: Microenvironment Discrepanciesmentioning
confidence: 99%
“…Azumi et al [61] found that miR-181a directly targets RASSF1, a MAPK signaling factor, and knockdown of RASSF1 increased sorafenib resistance. MiR-429 [62] promotes liver tumour-initiating cell properties by targeting Rb binding protein 4, and the ectopic expression of miR-484 [63] initiates tumourigenesis and cell malignant transformation through the synergistic activation of the transforming growth factor-β/Gli and nuclear factor-κB/type I IFN pathways to enhance chemotherapeutic resistance and increase tumorigenicity.…”
Section: Epigenetic Regulation Involved In Drug Resistancementioning
confidence: 99%